IMMU-48. GLIOMA IMMUNE PROFILING REVEALS UNIQUE IMMUNE THERAPEUTIC OPPORTUNITIES. (5th November 2018) - Ott, Martina; Zhou, Shouhao; Wei, Jun; de Groot, John; Huse, Jason T; McCutcheon, Ian; Prabhu, Sujit; Ferguson, Sherise; Weinberg, Jeffrey; Sawaya, Raymond; Rao, Ganesh; Lang, Frederick; et al.
Abstract: INTRODUCTION: There is a rapidly evolving portfolio of immune therapeutic modulators, but the relative incidence of immune targets in human gliomas is unknown. To prioritize available immune therapeutics, comprehensive immune profiling across glioma grades was conducted. METHODS: CD4+ and CD8+ T-cells and CD11b+ monocytes/macrophages were isolated from the blood of healthy donors (n= 6) and the blood and tumors of newly diagnosed and recurrent grade II (n= 7), III (n= 6) and IV glioma patients (n= 12), and profiled for the expression of 30 immune modulatory targets. RESULTS: In CD4+ and CD8+T-cells, PD-1 and the adenosine pathway showed high expression levels in tumor-infiltrating lymphocytes (TILs) across glioma grades and treatment states. The mean fluorescent intensity (MFI) of A2aR was appreciably upregulated in the TIL and in the CD11b+ glioma-infiltrating monocytes/macrophages (GIM) compared to healthy donors (CD4+ p = 0.0201; CD8+ p = 0.0233; CD11b+ p = 0.0009) and matched peripheral blood (CD4+ p = 0.0054; CD8+ p = 0.019; CD11b+ p < 0.0001). LAG3 and TIM3 TIL expression frequency was low and not associated with glioma grade. TIGIT CD8+TIL were more frequent in high-grade gliomas (grade III and IV). CD39 was upregulated in the TIL compared to healthy donors (CD4+ p =0.0032; CD8+ p =0.0006) and matched peripheral blood (CD4+ p = 0.0002; CD8+ p < 0.0001). B7-H3 ( p = 0.0167) and Galectin-9 GIM expression ( p = 0.0042) are frequently upregulated in glioblastoma. Regardless of glioma grade, the T-cell co-stimulatory molecule CD86 is down-regulated in the GIM ( p = 0.0019). Many immune modulatory markers were not frequently upregulated but exceptionally high in individual patients. CONCLUSION: Predicated on expression frequency, immune therapeutics targeting PD-1 and the adenosine pathway would be applicable to most glioma patients regardless of grade or prior treatment status. Clinical trials considering the use of other immune targets, such as LAG3, TIM3, TIGIT, BTLA, B7-H3, and Galectin-9 need to consider a companion biomarker for enrollment enrichment.